2008
DOI: 10.1016/j.drugalcdep.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Reward-related decision-making deficits and elevated impulsivity among MDMA and other drug users

Abstract: Background-The recreational drug, MDMA (3,4-methylenedioxymethamphetamine; 'Ecstasy'), is a synthetic amphetamine derivative and a serotonin neurotoxin. MDMA use is associated with cognitive dysfunction and impulsivity, but since polydrug abuse is common among users it is difficult to attribute these problems specifically to MDMA. Moreover, few studies have examined rewardrelated cognitive processes. Our aim was to examine reward-related decision-making and impulsivity among MDMA users while controlling for po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 91 publications
(129 reference statements)
2
64
0
5
Order By: Relevance
“…The most pronounced gray matter volume reductions in the present study have been found in the OFC and the DLPFC, which have consistently been linked to decision making (Ersche et al, 2005;Koechlin and Hyafil, 2007;Rogers et al, 1999;Schoenebaum and Roesch, 2005). MDMA and amphetamine users have repeatedly been shown to display qualitative poorer decision making compared to controls in terms of outcome (Ersche et al, 2005;Grant et al, 2000;Hanson et al, 2008;Moeller et al, 2007;Ornstein et al, 2000;Rogers et al, 1999;Quednow et al, 2007) and Specific drug use patterns of low exposure-and experienced users. a F-values with posthoc test (Scheffé); b t-values were calculated using unpaired t-test; 2-tailed (df = 60); c comparison tested with χ 2 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The most pronounced gray matter volume reductions in the present study have been found in the OFC and the DLPFC, which have consistently been linked to decision making (Ersche et al, 2005;Koechlin and Hyafil, 2007;Rogers et al, 1999;Schoenebaum and Roesch, 2005). MDMA and amphetamine users have repeatedly been shown to display qualitative poorer decision making compared to controls in terms of outcome (Ersche et al, 2005;Grant et al, 2000;Hanson et al, 2008;Moeller et al, 2007;Ornstein et al, 2000;Rogers et al, 1999;Quednow et al, 2007) and Specific drug use patterns of low exposure-and experienced users. a F-values with posthoc test (Scheffé); b t-values were calculated using unpaired t-test; 2-tailed (df = 60); c comparison tested with χ 2 .…”
Section: Discussionmentioning
confidence: 71%
“…Another frequently reported issue refers to the finding that ATS users show signs of disinhibition and elevated impulsivity on laboratory tests. Besides poorer performance of ATS users on these tests (Hoffman et al, 2006;Ornstein et al, 2000), results have also been linked to differences in structure (Hanson et al, 2008;Hesslinger et al, 2002;Salo et al, 2007;Quednow et al, 2007) and activation (Aron and Paulus, 2007;Ersche et al, 2005) of the orbitofrontal and anterior cingulate cortices in functional MRI studies. Furthermore, poor quality of decisionmaking, disinhibition and elevated impulsivity have consistently been described as core aspects of drug use initiation and the transition from recreational use to addiction (Grant et al, 2000;Hoffman et al, 2006;Schoenebaum et al, 2006).…”
Section: Tablementioning
confidence: 95%
“…For example, ecstasy users revealed elevated impulsivity on the Matching Familiar Figures Test (MFFT) (Morgan et al 1998;Morgan et al 2002;Morgan et al 2006;Quednow et al 2007) and on trait impulsivity (Morgan et al 1998;Parrott, 2000b;Butler and Montgomery, 2004) (Dafters, 2006;Vollenweider 1998), and on trait impulsivity . Previous studies also found that polydrug users, including users who had or had not used ecstasy, reported similar levels of impulsivity (Morgan et al 1998;Tuchtenhagen et al 2000;Daumann et al 2001;Morgan et al 2002;Butler and Dafters et al 2004;Hoshi et al 2007a;Hanson et al 2008), suggesting that elevated impulsivity may characterise drug users in general and not specifically those who have a history of ecstasy use.…”
Section: Introductionmentioning
confidence: 83%
“…The use of several of these drugs have been associated with significantly elevated levels of impulsivity, which are regarded as having dysfunctional and detrimental effects on neuropsychological performance measures (see Verdejo-García et al 2004 for reviews). MDMA use has been associated with significant declines on measures of processing speed, verbal fluency, working memory, reflection impulsivity and decision making in recreational users (De Sola et al 2008;Fisk and Montgomery 2009;Hanson et al 2008;Quednow et al 2007). Nevertheless, some of these effects have been attributed to the frequent co-abuse of cannabis among MDMA recreational users (Clark et al 2009;Croft et al 2001; see Gouzoulis-Mayfrank and Daumann 2006 for a review).…”
Section: Introductionmentioning
confidence: 98%